Influence of Sea Ice Crack Formation on the Spatial Distribution of Nutrients and Microalgae in Flooded Antarctic Multiyear Ice. Issue 2 (6th February 2018) - Nomura, Daiki; Aoki, Shigeru; Simizu, Daisuke; Iida, Takahiro
Abstract: Cracks are common and natural features of sea ice formed in the polar oceans. In this study, a sea ice crack in flooded, multiyear, land‐fast Antarctic sea ice was examined to assess its influence on biological productivity and the transport of nutrients and microalgae into the upper layers of neighboring sea ice. The water inside the crack and the surrounding host ice were characterized by a strong discoloration (brown color), an indicator of a massive algal bloom. Salinity and oxygen isotopic ratio measurements indicated that 64–84% of the crack water consisted of snow meltwater supplied during the melt season. Measurements of nutrient and chlorophyll a concentrations within the slush layer pool (the flooded layer at the snow‐ice interface) revealed the intrusion of water from the crack, likely forced by mixing with underlying seawater during the tidal cycle. Our results suggest that sea ice crack formation provides conditions favorable for algal blooms by directly exposing the crack water to sunlight and supplying nutrients from the under‐ice water. Subsequently, constituents of the crack water modified by biological activity were transported into the upper layer of the flooded sea ice. They were then preserved in the multiyear ice column formed by upward growth of sea ice caused by snow ice formation in areas of significant snow accumulation. Plain Language Summary: Formation of cracks in sea ice affects the environment associated with biological production and biogeochemical cycling in the surface ocean of sea ice systems. Because cracks are likely to form frequently within the sea ice during the season of ice melting and ice breaking, the contributions of cracks to biological production and biogeochemical cycling may be significant in ice‐covered oceans. In the future, the melting of sea ice in polar oceans will strongly affect the output of biogeochemical parameters trapped within sea ice and their use in primary and secondary production within surface oceans. In the case of multiyear, land‐fast ice, biogeochemical parameters that accumulate within the ice would be discharged abruptly to ocean surface waters when the multiyear ice breaks up. Key Points: Cracks in sea ice resulted in high chlorophyll concentrations in slush up to a few meters from the crack The 64–84% of the crack water consisted of snow meltwater supplied during the melt season Nutrient and chl a within slush revealed the intrusion of water from the crack